2017
DOI: 10.1101/110023
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FUMA: Functional mapping and annotation of genetic associations

Abstract: A main challenge in genome-wide association studies (GWAS) is to prioritize genetic variants and 1 identify potential causal mechanisms of human diseases. Although multiple bioinformatics 2 resources are available for functional annotation and prioritization, a standard, integrative approach 3 is lacking. We developed FUMA: a web-based platform to facilitate functional annotation of 4 GWAS results, prioritization of genes and interactive visualization of annotated results by 5 incorporating information from mu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…1a). These SNPs were found in 187 independent loci, identified using FUMA (Supplementary Table 2); [49,36] this represents an increase of 169 loci compared to those reported in the Sniekers et al GWAS alone [16]. In order to determine if differences in loci construction were influencing the difference across the intelligence (Sniekers), education (Okbay), and present study, we performed FUMA (using the same parameters as in the current study) on the Sniekers and Okbay datasets and compared the loci found across phenotypes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1a). These SNPs were found in 187 independent loci, identified using FUMA (Supplementary Table 2); [49,36] this represents an increase of 169 loci compared to those reported in the Sniekers et al GWAS alone [16]. In order to determine if differences in loci construction were influencing the difference across the intelligence (Sniekers), education (Okbay), and present study, we performed FUMA (using the same parameters as in the current study) on the Sniekers and Okbay datasets and compared the loci found across phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Using the meta-analytic dataset produced by MTAG, genetic loci related to intelligence were identified using FUMA [36]. First, independent significant SNPs were identified.…”
Section: Identification Of Independent Genomic Loci and Functional Anmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess whether the 12 prioritized genes from family P2 converge on biological shared functions, we tested for enrichment in Gene Ontology (GO) terms for biological processes using FUMA [42]. Overrepresentation of biological functions of prioritized genes was tested for by comparison with gene-sets obtained from the Molecular Signature Database (MsigDB) v5.2 (i.e., GO gene sets), using hypergeometric tests.…”
Section: Gene Ontology Enrichment Analysismentioning
confidence: 99%
“…Tissue enrichment analysis was conducted using FUMA 51 . Enrichment for pathways and ontologies was performed in EnrichR 27,28 using the human genome as the reference set and a minimum number of 2 genes per category.…”
Section: Gene Pathway and Tissue-enrichment Analysesmentioning
confidence: 99%